Effect of Ancillary Ligands on the Electronic Structures, DNA-binding and Spectral Properties of [Ru(L)2(atatp)]2+ (L = phen, bpy, dmp, tfp) - Miao, Ti-Fang; Li, Jun; Lu, Yu-Ting; Zheng, Kang-Cheng (Asian Journal of Chemistry, 2012)
The effect of ancillary ligands on the electronic structures and DNA-binding properties of Ru(II) polypyridyl complexes [Ru(L)2(atatp)]2+ (atatp = acenaphtheno (1,2-b)-1,4,8,9- tetraazatriphenylene; L = phen (1,10-phenanthroline), bpy (2,2'-bipyridine), dmp (2,9-dimethyl- 1,10-phenanthroline) and tfp (2,9-trifluoromethyl-1,10-phenanthroline) has been investigated, using the density functional theory (DFT) at the B3LYP/LanL2DZ level. The electronstructural characteristics and the trend in the DNA-binding constants (Kb) of these complexes were revealed. Based on the theoretical results, a new Ru(II) complex [Ru(tfp)2(atatp)]2+ (tfp =2,9-trifluoromethyl-1,10-phenanthroline)] with stronger DNA-binding ability was designed. In particular, the electronic absorption spectra of these four complexes in aqueous solution were exactly simulated using the time dependent density functional theory (TDDFT) method and the effect of the ancillary ligands on the spectra was investigated. The simulated absorption spectra of these complexes in aqueous solution are in a satisfying agreement with the experimental results and experimental absorption bands were theoretically explained in detail. These results help to directing functional molecular design as well as understanding the electron-structures and related properties of this kind of Ru(II) complex.